Associations between blood ethylene oxide levels and bone mineral density - Chen, Wenwen; Lu, Sujuan; Lin, Min; Chen, Kun; Huang, Feng (Frontiers in Public Health, 2025)
BackgroundEthylene oxide (EO) is a toxic compound extensively used in industrial applications. This study quantified serum EO levels by measuring hemoglobin-bound ethylene oxide (HbEO). However, the link between bone mineral density (BMD) and HbEO levels remains unexplored.MethodsA total of 2,570 participants were evaluated using data from National Health and Nutrition Examination Survey (NHANES) (2015–2018). Generalized linear regression models (LRM) and restricted cubic spline (RCS) analyses were used to investigate the association between blood EO levels and BMD. Adjusted models were also applied for comprehensive analysis.ResultsBlood EO levels and BMD were inversely related (p = 0.007). This RCS analysis also showed an L-shaped dose–response correlation between EO levels and BMD (p for nonlinearity <0.001).ConclusionThis study highlights a substantial correlation between EO exposure and BMD. Further randomized controlled trials are required to establish a causal relationship.